Finance and Stability: The Limits of Capitalism - Hyman P. Minsky (Levy Economics Institute of Bard College, 1993)
Once again the United States economy is facing a crisis, resolution of which first requires the realization that there are many types of capitalism: Solutions implemented in the past, therefore, may or may not be an appropriate solution today, as they could have been implemented as an answer to a problem posed within the context of a different model. Alternatively, the solution may lie in the implementation of a totally new economic regime in answer to reoccurring problems inherent in capitalism in general. The implementation of a new model is not a unique happening in United States economic history. The interventionist model-set in motion by President Roosevelt in answer to the failure of the laissez-faire model in the 1930s-dealt with the obvious flaw inherent in capitalism in general namely, its inability to maintain a level of aggregate demand consistent with full employment. Implementation of the interventionist model prevented a massive depression of the type experienced in the 1930s from being repeated due to the larger role played by the government sector in maintaining demand via active fiscal policy, while moderating inflation through the use of monetary policy. The interventionist model also recognized the less obvious, deeper flaw of capitalism-namely, the manner in which the financial system can adversely affect the price of assets relative to that of current output. Absent any interventionist policy, the resulting decline in private investment and profits leads to a downward spiral and collapse of the financial sector. The institutional roadblocks included in the interventionist model were sufficient to avert large disequilibriums in asset and output prices, thereby sustaining profits and precluding a deep recession. (Indeed, the Federal Reserve was not forced to act to avert a financial crisis until 1968, when problems arose in the commercial paper market.) The interventionist model, however, was abrogated during the 1980s with the reinstitution of a new laissez-faire model. The new model eliminated many of the restrictions imposed on financial sector, massive increases in national deficits through unproductive public sector spending (made even more inefficient by the resulting interest on the debt), and the growth of speculative financing schemes that left us with too many highly indebted firms. A large, financially induced depression was contained only through the reintroduction of massive governing monetary and fiscal intervention in the form of the S&L bailout and the maintenance of profits with massive deficits. Although the subsequent drop in interest rates has resulted in a rise in asset values and somewhat abated the turmoil in the financial markets, the economy continues to stagnate.
Keywords: 330